Utilização de efluente de piscicultura na irrigação De pimentão cultivado com fosfato natural e Esterco bovino - Lima, Cybelle Barbosa de (Universidade Federal Rural do Semi-Árido, 2007)
The fish effluent discharge in the environment may causing soil and water pollution resulting in environment impacts. One alternative to solve the problem of fish effluent discharge is their use to irrigate plants. The use of fish effluent to irrigate plants can be also one alternative to solve the problem of water scarcity in arid and semi-arid regions, making the system more sustainable and bringing incomes to the producer. Since the fish effluent is rich in microorganisms, organic mater and nutrients, as phosphorus and nitrogen, the effluent may function as a fertigation for the plants. The objective of this experiment was to evaluate the use of fish effluent to irrigate bell pepper, fertilized with cow manure andnatural phosphate to determine the advantage of this integration in a semi-arid region. A randomized complete block design, with two replications within of each block, in a split plot the scheme was used. To the plots were assigned two types of water (well water and fish effluent) and to the subplots, treatments of a 2X2 factorial arrangement, resulting from the combination of two levels of phosphate (with and without natural phosphate) with two levels of organic matter (with and without cow manure). The total experiment area was 768 m2. Each experimental unit consisted of four rows with a total area of 16 m2. The harvest area of the experimental unit was 6 m2, constituted for two central rows. In each row final part disregarded 0,50m. The cro management practices were performed according to the region recommended techniques for bell pepper plants. The following characteristics were evaluated: number of flowers per plant, number of fruits per plant, relationship fruit and flower, fruit number, fruit weight, fruit mean weight and productivity. The cow manure or natural phosphate fertilization, as well as the bell pepper plants irrigation with fish effluent irrigation, not provided significant increase in the number of flowers and fruits for plant. The natural phosphate fertilization and the bell pepper plants irrigation with fish effluent reduced the fruits productivity. Did not observe any significant interaction between water types and the natural phosphate or cow manure fertilization in the number of flowers or fruits for plants and bell pepper productivity
Use of fish effluent to irrigate bell pepper plants cultivated with natural phosphate and cow manure
Keywords: Capsicum annum; Fish effluent; Natural phosphate; Integration of aquaculture and agriculture; Capsicum annum; Efluente de piscicultura; Fosfato natural; Integração da agricultura com aqüicultura; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA